Indigenous university students' perceptions regarding nature, their daily lives and climate change: a photovoice study - Ieda M. A. V. Dias; Antonio Jose Grande; Paulo T. C. Jardim; Alessandra Aparecida Vieira Machado; Jacks Soratto; Maria Inês da Rosa; Luciane Bisognin Ceretta; Leonardo Roever; Xanthi Zourntos; Seeromanie Harding (BMC Public Health)
Abstract Background Climate change has severe health impacts, particularly for populations living in environmentally sensitive areas such as riversides, slopes, and forests. These challenges are exacerbated for Indigenous communities, who often face marginalisation and rely heavily on the land for their livelihoods. Despite their vulnerability, the perspectives of Indigenous populations on climate change and its impacts remain underexplored, creating a critical gap in the literature. This study explored the perceptions of Indigenous Brazilian university students on how climate change affects their daily lives and gathered their insights on potential adaptations to mitigate climate change-related impacts. Methods Using a participatory arts-based approach, participants captured photographs reflecting their lived experiences with climate change. Follow-up interviews provided a narrative framework for qualitative analysis, enabling participants to articulate the strengths and concerns of their communities while transcending cultural and linguistic barriers. Results The study revealed key themes, including (1) the fragility of ecosystems critical to Indigenous livelihoods, (2) the erosion of traditional knowledge systems due to environmental and social disruptions, and (3) the need for community-driven strategies to protect territories and preserve cultural identities. Participants highlighted the interconnectedness of their cultural values with environmental stewardship, emphasising the importance of maintaining these relationships as a form of resilience. Conclusion This study underscores the importance of protecting Indigenous territories and respecting their cultural identities to safeguard their survival and traditions. The voices of Indigenous university students provided valuable insights into community-based adaptations and strategies for mitigating the impacts of climate change.